2018
DOI: 10.1038/s41586-018-0211-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of mitochondrial receptor binding and constriction by DRP1

Abstract: Summary Mitochondrial inheritance, genome maintenance, and metabolic adaptation depend on organelle fission by Dynamin-Related Protein 1 (DRP1) and its mitochondrial receptors. DRP1 receptors include the paralogs Mitochondrial Dynamics 49 and 51 (MID49/MID51) and Mitochondrial Fission Factor (MFF), but the mechanisms by which these proteins recruit and regulate DRP1 are unknown. Here we present a cryoEM structure of human, full-length DRP1 coassembled with MID49 and an analysis of structure- and disease-based … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
292
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 270 publications
(306 citation statements)
references
References 76 publications
12
292
2
Order By: Relevance
“…Long‐range helical imperfections also limit the useable information in the power spectrum of the helix, leading to difficulties in indexing, which is a necessary step in generating initial models for the iterative reconstruction, though some brute‐force real‐space search procedures have been successful in identifying helical parameters. The results of these advances and others are that near‐atomic‐resolution reconstructions of lipid‐ and GMPPCP‐bound human dynamin 1 ΔPRD (3.75 å; Figure B), Drp1‐MiD49 co‐filaments (4.2 å; Figure D) and MxB polymers (4.6 å; Figure A) have recently been achieved by cryo‐EM. These models have supported the generation and refinement of detailed atomic models for how the DRPs assemble to generate their respective higher order assemblies.…”
Section: X‐rays and Cryo And Structures Oh My!mentioning
confidence: 99%
See 3 more Smart Citations
“…Long‐range helical imperfections also limit the useable information in the power spectrum of the helix, leading to difficulties in indexing, which is a necessary step in generating initial models for the iterative reconstruction, though some brute‐force real‐space search procedures have been successful in identifying helical parameters. The results of these advances and others are that near‐atomic‐resolution reconstructions of lipid‐ and GMPPCP‐bound human dynamin 1 ΔPRD (3.75 å; Figure B), Drp1‐MiD49 co‐filaments (4.2 å; Figure D) and MxB polymers (4.6 å; Figure A) have recently been achieved by cryo‐EM. These models have supported the generation and refinement of detailed atomic models for how the DRPs assemble to generate their respective higher order assemblies.…”
Section: X‐rays and Cryo And Structures Oh My!mentioning
confidence: 99%
“…Furthermore, Drp1 G362D, which harbors a mutation within Stalk Loop 1, thereby disrupting Interface 3, assembles into closed rings. In the presence of GMPPCP, stable rings were obtained of this mutant, which permitted the reconstruction of the predominant, 12‐membered form . In this case, Interface 2 was, indeed, conserved in conformation but extensive tilting at Interfaces 1 and 3 was observed to account for the turn between adjacent dimers.…”
Section: The Stalk: the Key To Assemblymentioning
confidence: 99%
See 2 more Smart Citations
“…However, although they are able to recruit drp1, it was found that the MiD receptors dissociate from the OMM during GTPase hydrolysis. It was discovered that overexpressing the MiD receptors can prevent mitochondrial fission . Fis1 is a protein first found to interact with the drp1 orthologue, Dnm1, in yeast, however, it was discovered that the interaction was not directly between drp1 and Dnm1, but rather through two adaptor molecules, Mdv1 and Caf4 .…”
Section: Quality Control In the Mitochondrionmentioning
confidence: 99%